Intervening factors in attention flow of professionals injured by biological material - Luana Cássia Miranda Ribeiro; Adenícia Custódia Silva e Souza; Anaclara Ferreira Veiga Tipple; Dulcelene Sousa Melo; Myrian Karla Ayres Veronez Peixoto; Denize Bouttelet Munari (SciELO, 2014)
Objective: To describe the barriers and facilitator factors to follow the attention flow of professionals injured by biological material in the worker perspective. Method: Qualitative descriptive study with data collected through individual interviews with 18 injured workers, assisted in reference public units in the city of Goiânia. The content analysis was carried out with assistance of the ATLAS.ti 6.2 software, under the work organization and subjective perspectives. Results: From the interviews regarding the barriers and facilitator factors emerged the categories: organizational structure, Support from close people, and Knowledge influence. Conclusion: The organized services have enabled more qualified consultations and the workers follow-up, which caused a satisfaction feeling in relation to the working environment.